ANALISIS KAPASITAS AIR SIDE RENCANA PENGEMBANGAN BANDAR UDARA INTERNASIONAL AHMAD YANI SEMARANG - Muchammad Ulil Aidi; Yahya Anas; Bagus Hario Setiadji; Wahyudi Kushardjoko (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Ahmad Yani Airport in Semarang is one of the international airport in the Province of Central Java . International airport status is used because there is a flight plan to foreign country and Ahmad Yani Airport worthy to serve the airlines. However, the facilities and services that exist not suitable for international-class airport. Therefore, these airports continue to be developed in order to serve the demand for overseas flight, both domestic and international flights increased from year to year. It can be from Semarang and head to Semarang. The development includes the development of the infrastructure of the airport land and air sides which are divided into two phases. With the completion of the first phase of development, Ahmad Yani Airport will have a wider terminal in the North of runway, ample parking space, covering an area of 61.344 m2 apron and two taxiways. Development of second phase will make Ahmad Yani Airport has an area of 78.313 m2 apron that can accommodate 12 Boeing 737-900 aircraft class and 8 pieces taxiways, 2 pieces exit taxiways and 1 piece parallel taxiway. This Final Thesis will analyze the air side of the Ahmad Yani airport that has runway formed, taxiway and apron at the existing condition, the development of the first phase and the second phase of development. This analysis will have predicted number of passengers in the plan of year which will then be converted into the number of aircraft at busy times. Results of the predicted number of aircraft will be on an analysis for the air side capacity of the Ahmad Yani Airport in the development plan that has been done by Ahmad Yani airport, so that it will be known the air side ability of the Ahmad Yani Airport to the demand in the plan year. This analysis refers to the rules that set up by FAA. Results of the analysis showed that when the condition of existing air side in the form of runway, taxiways are still able to serve the demand of flight but the capacity of the apron are not able to serve so for prediction of the next 5 years in the first phase of development there will be over capacity. However, with the development at the Ahmad Yani Airport, aircraft servicing predictions for the next 5 to 10 years can already be served by a taxiway and apron but rapid exit taxiway should be built for runway’s component, so that it can increase runway capacity at peak hours.